Prenatal detection of mild fetal ventriculomegaly – a systematic review of the modern literature - Sapantzoglou, Ioakeim; Asimakopoulos, Georgios; Fasoulakis, Zacharias; Tasias, Konstantinos; Daskalakis, Georgios; Antsaklis, Panagiotis (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Introduction While mild fetal ventriculomegaly is frequently observed as an incidental and benign finding, it is also known to be linked with structural, genetic, and neurodevelopmental abnormalities. The objective of this study was to conduct a systematic review of the existing literature in order to evaluate the association between apparently isolated fetal mild ventriculomegaly with the presence of additional structural defects detected by fetal brain MRI, chromosomal or other genetic anomalies, and neurodevelopmental delay.Methods This systematic review was designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Modern literature was searched from January 1, 2011, to July 31, 2023.Results 23 studies were included, comprising a total of 2590 patients. Nine studies assessed the association between fetal mild ventriculomegaly and neurodevelopmental impairment, including 536 cases, with normal neurodevelopmental outcomes ranging from 64% to 96.5%. Ten studies evaluated the additive value of fetal MRI, including 1266 fetuses, with the detection rate of additional brain defects that eventually altered the clinical management ranging from 0% to 19.5%. Seven studies investigated the association of mild ventriculomegaly with the presence of underlying chromosomal or genetic conditions, including 747 cases, with the rate ranging from 1.1% to 15.4%.Conclusion The prevalence of aneuploidy and genetic abnormalities in ventriculomegaly, especially in isolated cases, is reported to be quite low and the incidence of neurodevelopmental delay appears to be similar to that of the general population in cases that are apparently and truly isolated.
Keywords: mild ventriculomegaly; fetal ventriculomegaly; dilatation; fetal ventricular system; isolated